Assessment of heavy metal pollution associated with tailing dam in gold mining area, southern ethiopia. Issue 1 (2nd January 2023) - Techane, Gera; Sahilu, Geremew; Alakangas, Lena; Mulat, Worku; Kloos, Helmut
ABSTRACT: Tailings dam is the main heavy metal pollution source in mining areas. In this study, the concentration of heavy metals in soil and water from upstream and downstream of the tailings dam was analyzed. The concentration of As, Cd, Cu, Ni, Pb, and W in tailings soil exceeded the standard value but Hg and Zn in the tailings soil were far below the standard. Average concentrations of As, Pb, and W in soil samples were above the upstream reference soil. The level of As and Pb decreases, downstream as the distance from the tailings dam increases. The mean concentrations of the heavy metals in water for Ni, Cu, Zn, Pb, and Cd were 106.3, 57.3, 21.8, 14.5, and 8.0 µg/L, respectively. The Ni contents in all studied water samples had concentrations higher than Awata River and WHO guidelines for drinking water. Both geo-accumulation and ecological risk indices have indicated significant heavy metal pollution in the study area. The overall results of this study showed that the soil and water downstream of the tailings dam were not safe and must be protected against access to humans and domestic animals.